Study of sustainable HDPE-based materials for aquaculture applications: effects on fouling - Sanjuan, Eva; Barriga-Cuartero, Javier; Andreu-Sánchez, Oscar; González, Alberto; Fouz, Belén (Frontiers in Marine Science, 2023)
This study addresses one of the most common problems faced by the marine sector, namely the accumulation of organic matter and organisms on submerged surfaces. This biological phenomenon causes structural problems in aquatic systems and its mitigation implies a large economic outlay for marine aquaculture industry. Antifouling paints are being developed to help control this undesirable process; however, these treatments are problematic as they degrade and release biocides and heavy metals into the environment. In this context, our study focuses on developing more environmentally friendly antifouling strategies. For this purpose, we designed high-density polyethylene (HDPE) material functionalized with different copper compounds or silica, and subsequently tested their effects on biofilm formation by aquatic organisms at both laboratory and pilot scale. Bacterial species (Vibrio harveyi and Cellulophaga lytica) and diatoms (Nitzschia ovalis) known for producing biofilm were used. Our study revealed that material including copper pyrithione (CuPT) was highly effective in inhibiting bacterial and algal biofilm formation. Moreover, the ecotoxicological study covering three trophic levels (bacteria, algae and rotifers) indicated that none of the materials developed and tested herein was toxic. HDPE is easily moldable and suitable to produce built-in aquatic structures, and our results show that its functionalization with CuPT greatly improves its antifouling capacity. These findings represent a step forward in the fight against fouling in marine environments.